ORGANIZING INDEPENDENT LEARNING ACTIVITIES IN AN ARTIFICIAL INTELLIGENCE BASED DIGITAL EDUCATIONAL ENVIRONMENT (Modern American Journal of Social Sciences and Humanities, 2026)
This article discusses the organization of independent learning activities in an artificial intelligence-based digital educational environment. It analyzes the role of modern digital technologies and artificial intelligence tools in education, as well as their importance in developing learners’ independent learning skills. The study highlights ways to improve the effectiveness of education through personalized approaches, adaptive learning platforms, and interactive methods.